Practical power system and protective relays commissioning - Atwa, Omar Salah Elsayed (Academic Press, 2019)
Practical Power System and Protective Relays Commissioning is a unique collection of the most important developments in the field of power system setup. It includes simple explanations and cost affordable models for operating engineers. The book explains the theory of power system components in a simple, clear method that also shows how to apply different commissioning tests for different protective relays. The book discusses scheduling for substation commissioning and how to manage available resources to efficiently complete projects on budget and with optimal use of resources.